Knowledge, perceptions, and management of cancer-related fatigue: the patients' perspective - Schmidt, Martina; Bergbold, Susanne; Hermann, Silke; Steindorf, Karen (Supportive care in cancer, 2021)
This study aimed to assess cancer patients’ knowledge and perceptions regarding fatigue and to provide up-to-date information on the current fatigue management from the patients’ perspective.
Online publiziert: 29. August 2020
Gesehen am 17.02.2026